The Longest Two Decades of the US: The Story of Four Crises - Kanat, Kılıç Buğra. author. aut Link
XVII, 355 p. 1 illus.
Keywords: This book chronicles the pivotal transformations in the United States from 2001 to 2021, with a particular focus on its evolving global image, internal political dynamics, and economic landscape. The phrase "the long two decades" describes a period characterized by a succession of four major crises that profoundly impacted American society and politics: the 9/11 attacks, the invasion of Iraq, the Great Recession, and the COVID-19 pandemic. Intriguingly, these contemporary crises parallel four significant events of the 20th century—Pearl Harbor, the Vietnam War, the Great Depression, and the Spanish Flu—that similarly reshaped the nation’s political and social landscape. The book provides historical contexts, examines the duration of these crises, and explores their aftermath effects on American society, while also underscoring the unique differences among them. Kılıç Buğra Kanat is Associate professor of Political Science at Penn State Erie, The Behrend College, USA. He was awarded the Outstanding Research Award and Council of Fellows Faculty Research Award at Penn State Behrend. He participated in the Future Leaders Program of Foreign Policy Initiative. Dr. Kanat’s writings have appeared in Foreign Policy, Insight Turkey, The Diplomat, Middle East Policy, Arab Studies Quarterly, Mediterranean Quarterly, Journal of South Asian and Middle Eastern Studies, Journal of Balkan and Near Eastern Studies, and Journal of Muslim Minority Affairs. He is a columnist at Daily Sabah. He is the author of A Tale of Four Augusts: Obama’s Syria Policy, Vulnerable Partnership: The History of US-Turkey Strategic Relations and Mapping the Fault Lines in Turkey-US Relations: Making the Vulnerable Partnership.